Distinct water mass between inside and outside eddy drive changes in prokaryotic growth and mortality in the tropical Pacific Ocean - Chen, Patrichka Wei-Yi; Olivia, Madeline; Gong, Gwo-Ching; Jan, Sen; Ho, Tung-Yuan; St. Laurent, Louis; Tsai, An-Yi (Frontiers in Marine Science, 2024)
Throughout the western tropical Pacific Ocean, eddies and currents play an important role in biogeochemical cycling. Many studies have investigated the effects of hydrography on vertical patterns of picophytoplankton and heterotrophic bacterial abundance in mesoscale eddies. There is a lack of field observations to determine what impact dynamic hydrological systems of eddies have on prokaryotic community activity (growth and mortality rates). An objective of this study was to examine how anticyclonic eddies influence picoplankton abundance and activity (growth and mortality rates). To meet this purpose, heterotrophic bacterial and picophytoplankton growth and mortality rates were examined by modified dilution experiments conducted at the surface, deep chlorophyll maximum (DCM), and 200 m depth outside (OE) and inside of warm eddies core (EC) in the west Pacific Ocean. A high heterotrophic bacterial grazing rate was found in the EC region in the present study. Furthermore, the picophytoplankton grazing rate in EC was frequently greater than the grazing rate in OE. Furthermore, the higher grazing rates in the EC region cause a lower proportion of viral lysis to account for heterotrophic bacteria and picophytoplankton mortality. The results of our experiments suggest that downwelling in EC might increase picophytoplankton growth and grazing rates, increasing the carbon sink in the warm eddy and potentially increasing ocean carbon storage.